2018
DOI: 10.1177/1559325818804361
|View full text |Cite
|
Sign up to set email alerts
|

Can Whole-Body Vibration Exercises in Different Positions Change Muscular Activity of Upper Limbs? A Randomized Trial

Abstract: The aim of this study was to investigate the acute effects of whole-body vibration exercises (WBVE) in different positions on muscular activity of flexor digitorum superficialis (FD), wrist extensor (ED), and handgrip strength (HG) of healthy men. Fifteen participants have performed 5 test sets each one consisting of HG strength measurement and 1-minute WBVE intervention (frequency: 50 Hz, amplitude: 1.53 mm, synchronous tri-planar oscillating/vibratory platform), that could be control (no exposition to vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(42 reference statements)
0
9
0
1
Order By: Relevance
“…We observed that mechanical vibration can be amplified as it is transmitted through the skeleton and that knee flexion is an important factor for limiting the amount of vibration energy reaching the head. We have not evaluated exercises involving vibration passed to the body while sitting on the platform (eg, abdominal crunches or sit-ups), 6 sitting off the platform with feet on the platform, 40,41 placing hands on the vibration platform (eg, planks or push-ups), 5,6,[42][43][44] or performing bicep curls and tricep extensions holding nylon straps attached to the vibration platform. 45 We advocate caution as these postures may result in excessive vibration energy reaching the head as the vibration is transmitted to the upper body, bypassing the knees and the vibration attenuation that knee flexion provides.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that mechanical vibration can be amplified as it is transmitted through the skeleton and that knee flexion is an important factor for limiting the amount of vibration energy reaching the head. We have not evaluated exercises involving vibration passed to the body while sitting on the platform (eg, abdominal crunches or sit-ups), 6 sitting off the platform with feet on the platform, 40,41 placing hands on the vibration platform (eg, planks or push-ups), 5,6,[42][43][44] or performing bicep curls and tricep extensions holding nylon straps attached to the vibration platform. 45 We advocate caution as these postures may result in excessive vibration energy reaching the head as the vibration is transmitted to the upper body, bypassing the knees and the vibration attenuation that knee flexion provides.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the effects of WBVE on HS are controversial. To the best of our knowledge, only one study has assessed the effects of WBVE in different positions (30 s of rest and 30 s of WBVE on the push-up, and squat conditions) on HS and muscular activity of FDSM in military soldiers ( Morel et al, 2018 ), and no positive effects being recorded.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most literature regarding EMGrms during WBVE has been focused on the lower extremity. By contrast, few studies have investigated the effects of vibration on the EMGrms of the upper extremity muscles so far ( Hand et al, 2009 ; Di Giminiani et al, 2014 ; Ashnagar et al, 2016 ; Morel et al, 2018 ). Bosco et al (1999) suggested the use of the ratio between EMGrms and HS, i.e., neural ratio (NR).…”
Section: Introductionmentioning
confidence: 99%
“…END (0-10) Inicial, média (DP) † † 1,8 (2,2) # 0 (0) END (0-10) Após Exercício BF, média (DP) † † 2,6 (2,8) £,# 0,1 (0,5) END (0-10) Após Fadiga Subjetiva, média (DP) † † 4,2 (3,3) £,# 0,6 (1,5) £ EBM (0-10) Após Exercício BF, média (DP) 2,5 (1,7) 1,5 (1,3) EBM (0-10) Após Fadiga Subjetiva, média (DP) 5 (2, (Anders et al, 2007;Sánchez-Zuriaga et al, 2009) provavelmente não foi suficiente para causar excitação dos motoneurônios alfa e consequentemente não gerou aumento da atividade EMG e da força muscular, bem como não afetou o SPA. A literatura aponta que o mesmo ocorre com a atividade EMG quando aplicada a vibração local no músculo bíceps braquial (Cochrane, 2016) e no tronco através de plataforma vibratória (Morel et al, 2018) de indivíduos saudáveis.…”
Section: Resultsunclassified